Food and water scenarios for the Karkheh River Basin, Iran - Marjanizadeh, S.; Fraiture, Charlotte de; Loiskandl, W. (Informa UK Limited, 2010)
Increasing population and income and a wheat self-sufficiency policy are already stressing Iran's strategic Karkeh River Basin. Examining three scenarios to the year 2025, the authors of this study find: (1) business as usual leads to an aggravation of groundwater overdraft and may jeopardize the ecosystem services provided by the Hawr Al Azim marsh area; (2) giving priority to environmental flow requirements and restoring groundwater tables leads to a shortfall in wheat production; but (3) reducing agricultural water demand could maintain a certain level of food production. Appropriate policy could minimize the tradeoffs between food self-sufficiency, sustainable water use and farmers' income.